Knowledge Awareness And Practice Regarding Bell's Palsy Among Dental Students In Chennai - NARAM, ABHISHEK; PRABU, DR. DINESH; S, DR. DEEPAK (The journal of contemporary issues in business and government, 2021)
Introduction:Bell’s palsy is an idiopathic, acute peripheral palsy of the facial nerve that results in muscle weakness on one side of the face, characterized by sudden onset, and unilateral facial paralysis, lower motor neuron weakness of the facial nerve with no other neurological abnormalities and no readily identifiable cause. The aim of this study was to measure the knowledge and attitude among dental students A self administered questionnaire consisting of 17 questions regarding knowledge and awareness of bell's palsy .Data was collected through google forms. responses were analysed and statistical data is represented as pie charts. From the results 69% of the people selected facial nerve is affected by bell's palsy and 75% of the people selected that bell's palsy affects only one side of the face and 25% disagreed with it. 60% of the study participants said that recovery duration of immediate type facial paralysis is 4 hours. The knowledge of anatomy, diagnosis and treatment was satisfactory and suggest that they have sufficient awareness. Dental students and dentists should be exposed to any medical condition that could happen because of iatrogenic reasons.